ANGKLUNG ROBOT CONTROL SYSTEM BASED ON MICROCONTROLLER - Efrat Murpratama; Unang Sunarya; Atik Novianti (Jurnal Elektro dan Telekomunikasi Terapan (e-Journal), 2019)
Angklung is an art tool made of bamboo originating from West Java. Although angklung has been known worldwide, even UNESCO (United Nations of Educational, Scientific, and Cultural Organizations) has designated the instrument as part of Indonesian original art, but unfortunately this traditional musical instrument is almost extinct. On the other hand, technological developments help and make it easier for humans to do anything. One form of technological development is robots. Therefore, this article will discuss about the design of the angklung robot control system. The design consists of two parts, namely the design of the angklung robot and the design of the angklung robot control application. Some components used in angklung robots include Bluetooth HC-06, Arduino Uno, and relay modules, while for Android-based control applications. The process of sending data from the application to the angklung robot using Bluetooth communication. The results show that the angklung robot control system can transmit data at a distance of less than 10 meters and with an average delay of 0.303 seconds. For the functionality of the 100% angklung robot control application it can work in accordance with the initial design.